The Effect of Using Karaoke Activities on Students’ English Pronunciation - Karsono, Karsono (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2019)
Karaoke is basically a form of entertainment involving the use of a karaoke machine which provides audio, visual, and also textual information at the same time. Having these features, karaoke offers some promising and potential uses to the language teaching, because it involves both linguistic processing and language articulation. This research aims at investigating the effect of karaoke activities on students’ English pronunciation. Employing the one-group pretest-posttest design, 34 students of the X MIPA 3 class of SMA Negeri 14 Jakarta in academic year 2018/2019 learnt pronunciation through karaoke activities in five sessions. Using Wilcoxon Sign Ranks Test, the hypothesis test revealed that karaoke activities significantly affected the tenth graders’ English pronunciation at SMA Negeri 14 Jakarta.